2020
DOI: 10.3390/genes11070815
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Granule Distribution and Expression Pattern of Genes Regulating Cellular Component Size, Morphogenesis, and Potential to Differentiation are Related to Oocyte Developmental Competence and Maturational Capacity In Vivo and In Vitro

Abstract: Polyspermia is an adverse phenomenon during mammalian fertilization when more than one sperm fuses with a single oocyte. The egg cell is prepared to prevent polyspermia by, among other ways, producing cortical granules (CGs), which are specialized intracellular structures containing enzymes that aim to harden the zona pellucida and block the fusion of subsequent sperm. This work focused on exploring the expression profile of genes that may be associated with cortical reactions, and evaluated the distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…This gene is necessary for meiotic maturation of porcine oocytes, particularly for reaching MII metaphase 60 . rs62359711 near DAB2 (Figure 4, maternal MII errors locus #8), which may be involved in oocyte maturation, particularly at MII, 58,59 follows a similar pattern. rs73178888 (Figure 4, maternal MII errors locus #9), also significantly associated with nondisjunction in all three MII subgroups, is located near DLGAP2 but is not in linkage disequilibrium with rs1612273 (discussed above in the combined MI and MII analysis); therefore, these associations may represent independent signals.…”
Section: Resultsmentioning
confidence: 90%
“…This gene is necessary for meiotic maturation of porcine oocytes, particularly for reaching MII metaphase 60 . rs62359711 near DAB2 (Figure 4, maternal MII errors locus #8), which may be involved in oocyte maturation, particularly at MII, 58,59 follows a similar pattern. rs73178888 (Figure 4, maternal MII errors locus #9), also significantly associated with nondisjunction in all three MII subgroups, is located near DLGAP2 but is not in linkage disequilibrium with rs1612273 (discussed above in the combined MI and MII analysis); therefore, these associations may represent independent signals.…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, XLOC_020079, XLOC_107361, XLOC_169844, XLOC_252348, and the target genes ( ARHGEF2 and RAPGEF6 ) were mainly associated with prolificacy. In vitro, culture studies of mammalian oocytes reveal a well-developed increase in ARHGEF2 in mature oocytes, suggesting that ARHGEF2 may affect the development and maturation of oocytes [ 69 ]. In addition, RAPGEF6 is essential for the high egg-laying rate of chickens [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a constant increase in peripheral CG density following oocyte maturation has been reported in mouse oocytes (Ducibella et al, 1988a(Ducibella et al, , 1994. In contrast, in in vitro matured pig oocytes, it has been shown that the mean value of the peripheral density of CGs during mid-oogenesis was less than in early oocytes (Kulus et al, 2020). This suggests that the acquisition of meiotic competence and progression correlates with a decrease in the number of CGs per 100 µm 2 of the ooplasmic cortex (Figure 2).…”
Section: Cortical Granule Biology Cg Biosynthesismentioning
confidence: 94%
“…Yet, during mid-oogenesis, a concentration twice higher of these secretory vesicles can be found at the cell periphery, suggesting their translocation from the central region toward the cortex. Moreover, CG translocation to the cortical area is associated with a high meiotic competence (Kulus et al, 2020). By analyzing fixed mouse oocytes, it has been shown that CG transport to the PM is a microfilament-dependent process (Connors et al, 1998;Wessel et al, 2002).…”
Section: Cg Transport and Cortex Accumulationmentioning
confidence: 99%